2009
DOI: 10.1295/polymj.pj2008321
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alkoxylated Phenolic Resins Containing an Acetyl Group and Their Functionalization by Grignard Reaction

Abstract: We successfully synthesized acetyl group-containing phenolic resins as novel reactive polymers. The addition-condensation of 2,4,6-trimethoxyacetophenone (1) with an equimolar amount of formaldehyde catalyzed by 12 mol/L HCl aq. proceeded homogeneously without side reactions to give polymer 3 (M n 4800, M w =M n 1.3) in 32% yield. The FT-IR, 1 H NMR and 13 C NMR spectra of 3 revealed that it had arylene-methylene units on the polymer backbones. The terpolymerization from 1, 1,3,5-trimethoxybenzene (2) and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The synthesis of a reactive trimethoxybenzene novolac having acetyl groups and their polymer reaction with a Grignard reagent are described in a separate paper. 16 …”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of a reactive trimethoxybenzene novolac having acetyl groups and their polymer reaction with a Grignard reagent are described in a separate paper. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to develop a high-performance LP, it is necessary to modify these functional groups. Previously, we demonstrated that phenolic resins prepared from phenol derivatives containing protected (alkoxylated) hydroxyl groups [13][14][15][16] exhibit higher thermostability; for example, it was demonstrated that 10% loss in weight (T d10 ) of alkoxylated-naphthalene-based resin occurs at a temperature greater than 400 1C. Further, alkoxylated-phenol-derivative-based phenolic resins exhibited good filmforming abilities and processabilities.…”
Section: Introductionmentioning
confidence: 99%
“…2,23 From this viewpoint, we have synthesized a wide variety of aromatic polymers from alkoxylated phenol derivatives such as anisole, phenethol and diphenyl ether by a method similar to acid-catalyzed phenol-formaldehyde condensation. 2,[23][24][25][26][27][28][29][30][31][32][33] The obtained polymers exhibit good solubility in organic solvents and they are more resistant to heat and oxidation than are phenolic novolacs. Furthermore, using hydroxyl-group-functionalized phenol derivatives, a functional novolac can be prepared by a one-step procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44][45][46] We have already reported the synthesis of reactive novolacs having a variety of functional groups such as formyl, 31 acetyl 32 and hydroxymethyl groups. 33 The development of such novel reactive novolacs can lead to novolacs finding significantly increased applications.…”
Section: Introductionmentioning
confidence: 99%